Production of beauvericina by Beauveria bassiana 9401 isolated from Lutzomyia sp.(Diptera:Psychodidoe) vectors of Leishmaniosis - URIBE-SOTO, SANDRA; SALDARRIAGA, YAMILE; PINEDA, FABIO; JAIME-ARANGO, GABRIEL; VÉLEZ, IVÁN DARÍO (Revista Colombiana de Entomología, 1997)
The in vitro production of the mycotoxin beauvericin by Beauveria bassiana 9401 originally isolated from Lit/zompa sp. (Diptera: Psychodidae) potential vector of Leishmaniosis was determined. The mycotoxin was detected in fractions obtained from crude extracts of dry mycelia. the identification and quantification of the mycotoxin was done by Liquid Cromatography High-Performance HPLC: approximately 2.7% of crude extract was beauvericin. The cytotoxic effects of beauvericin in Aedes alhopictus C6/36 cell line defined as morphological alterations and diminution in cellular viability were demonstrated, the CL50 value of a fraction with 10% of beauvericin for cells was estimated as 25 ne/ml.